Aneurysm of the Superior Labial Artery - Seidel, Amelia Cristina; Rossetti, Leandro Pablos; Mangolim, Amanda Sampaio; Gomes, Juliana Regina; Rollo, Hamilton Almeida [UNESP] (Elsevier B.V., 2012)
This is a case report of a true and dissecting aneurysm of the superior labial artery in a 51-year-old patient without risk factors for vascular pathology. The patient complained of swelling of the upper lip, mostly on the left side. A Doppler ultrasonography was used in the diagnosis. The definitive treatment was surgical resection, and the histopathological analysis confirmed the diagnosis. The progress of the patient was satisfactory, leaving a slight change in sensitivity in the area. This seems to be the first reported case of true and dissecting aneurysm of the superior labial artery in the medical literature.